2005
DOI: 10.1007/978-3-540-30569-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Mastering Test Generation from Smart Card Software Formal Models

Abstract: Abstract. The growing complexity of new smart card platforms, including multi-subscription or multi-application functionalities, led up to more and more difficulty in testing such systems. In previous work, we have introduced a new method for automated test generation from statebased formal specifications (B abstract machines, UML/OCL models, Z specifications). This method uses cause-effect analysis and boundary computation to produce test cases as sequences of operation invocations. This method is embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Model-based testing can be easily introduced to the development process of the smart card, automatic test generation process saves 30% of labor when modeling task is included compared with manual testing. However, model-based testing is limited to functional testing [19]. Martin and Bousquet (2001) proposed a solution for JSC applet validation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Model-based testing can be easily introduced to the development process of the smart card, automatic test generation process saves 30% of labor when modeling task is included compared with manual testing. However, model-based testing is limited to functional testing [19]. Martin and Bousquet (2001) proposed a solution for JSC applet validation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Van Weelden, et al (2005) showed that automated, formal, specification-based testing of smart card applets is feasible, and that errors can be detected [21]. Bouquet, et al (2005) focused on functional testing based on formal models of functional specifications of the software under test to automatically generate test data. Functional testing aims at ensuring the correctness of operations and their conformance to the functional requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [8] represents results on the CEPS standard, [3] shows validation results on the GSM 11.11 standard [12], [31] used automated test generation on the WAP Identity Module, [5] describes techniques which can be apply at different levels of smart card software, [6] represents an automatic test generation with the LEIRIOS tool [26] from B specifications, [29] presents a method to automatically generate test for Java card applets and [7] offers a semi formal model of Java Card applications in UML.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the formal semantics of the BT notation has been stressed from the beginning; a formal semantic language Behavior Tree Specific Language (BTSL) has been developed [11], and a BT can be automatically translated into formal languages such as CSP [9] and SAL [10], and described by a metamodel [8]. Even though a BT is a formal specification, unlike formal languages such as CSP, SAL or B notation [41], the flowchart-styled graphic notation of BT can be easily understood by non-experts. Therefore, the BT notation has both advantages as a formal language with precise semantics so it can be mechanically checked, analyzed and simulated, as well as a soft and casual modeling [5] that non-technical stakeholders find appealing.…”
Section: The Behavior Tree Design Approachmentioning
confidence: 99%